PENGAMANAN FILE MENGGUNAKAN DIGITAL SIGNATURE ALGORITHM (STUDI KASUS : WITDIA SOLUSI INDONESIA) - Seno Agung Prakoso, - (2019)
This study was conducted in sending the file tender for giving a project offer which is a confidential file without a security for the file. Technology development in the ease way in sending file using media eletronic gived a hole for the security, more than that if the file is a confidential file. In this case, many companies who File tender is a classified file that contain a submission for offer, a project this file is PDF file. Therefore this file needs to be secured for confidentiality and authenticity with Cryptography. Cryptography is the pratice and study of techniques for secure information by encoding the messages that the meaning cannot be read or understood. In the process for secureting file tender with Cryptography Digital Signature Algorithm which used asymmetry keys. Digital signature algorithm haved two keys that needed in Encryption and Decryption process. In Digital signature algorithm encryption process Digital signature algorithm will generated chipertext, and with decryption process this chipertext neutralized back into beginning file plaintext. The with this the hole in sending file in media eletronic being solved and secured